Cross-sectoral collaboration in the planning phase of the Hippos2020 project in Jyväskylä - Ruuskanen, Noora (2018)
Sport planning is recognized to be one way how a municipality can affect on its residents’ level of physical activity and the general health of community. Moreover, creative sports facility planning and construction can have positive impacts on the citizens’ volition to practice sports. Due the tightened economic situation, the municipalities nowadays do not have enough resources to implement major sports projects, such as the construction of multipurpose arenas or big stadiums. The help of private sector is needed in order to secure adequate sports services for recreational hobbyists as well as for elite athletes. The Hippos2020 project will be Jyväskylä’s biggest investment ever in sports and wellbeing, and it aims to implement a nearly 300M€ plan by constructing a new concentration of sports, physical activity, health, wellbeing, research, and commercial services right in the middle of the city. A new partnership method is required to manage, develop, and finance the extensive project plan. Thus, this study aims to examine the roles of different sectors that work closely together in order to make the project possible. A qualitative content analysis is used as method to categorize various subjects and to create specific themes based on the research findings. Quantitative research material, such as statistics and expense calculations, as well as qualitative material, such as public documents and memos, are analysed in order to perceive an overall scope of the picture of Hippos2020 project. In addition, qualitative theme interviews are conducted to gain deeper understanding of the forms of cooperation between the sectors. Five selected interviewees represent public, private, and third sectors, and deepen the understanding of the involvement and roles of each sector. Results show that each sector has its own specific role in the planning phase of the Hippos2020 project. The public sector acts as starter of the development process, and later its role changes to the contracting entity and a decision-maker. The private sector becomes involved as a producer of the preliminary investigation report, and later extends its role to the main financier of the project. In addition, the third sector participates in the planning by giving practical guidance of what kinds of facilities the final users need, and by emphasizing the fact that the new facilities should be affordable enough so that the club activities can be operated there. The culmination points of cross-sectoral collaboration in the Hippos2020 project are especially the creation of the hybrid concept for the area, the establishment of the Hippos Developmental Company, and the innovation partnership phase. As a result of the cross-sectoral collaboration, a new way of tendering a public procurement is used and it proves to be quite successful. Based on the experiences of the usage of the innovation partnership model in the Hippos2020 project, it can be suggested that the same method could work in similar size or type of construction projects also in other fields. However, more research is required to confirm the applicability of the model, as well as its benefits and disadvantages. Also, the applicability of the Public-Private-People Partnership model in sports related projects needs more academic support.